2013
DOI: 10.6063/motricidade.9(4).689
|View full text |Cite
|
Sign up to set email alerts
|

Relação da maturação com a antropometria e aptidão física na iniciação desportiva

Abstract: RESUMOO presente estudo centra-se em verificar a influência da maturação na antropometria e aptidão física de jovens praticantes de voleibol, observando a correlação do estado maturacional com as demais variáveis. A amostra do estudo foi composta por 149 sujeitos (n= 149) de 8 a 14 anos. Para verificação da maturação, utilizou-se a idade cronológica e idade óssea como preditor maturacional através do método Grave-Brown (1976). Por sua vez, para as variáveis antropométricas, foram usadas as medidas de massa, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
7
0
3
Order By: Relevance
“…However, after body mass and height inclusion to the model, a small correlation coeicient increase was evidenced, demonstrating that skeletal age is able to explain the greater variance in upper and lower limbs explosive strength, with lower variance shared for vertical jump. Previous studies of our group 10,25 showed similar relation between lower limbs explosive strength and biological development has presented lower coeicients when compared to upper limbs explosive strength. Till et al 5 did not verify interaction efect for maturational group x time efect for vertical jump when they compared annually young rugby players performance in respective categories (under 13, under 14 and under 15) according to maturational stage.…”
Section: Discussionmentioning
confidence: 94%
“…However, after body mass and height inclusion to the model, a small correlation coeicient increase was evidenced, demonstrating that skeletal age is able to explain the greater variance in upper and lower limbs explosive strength, with lower variance shared for vertical jump. Previous studies of our group 10,25 showed similar relation between lower limbs explosive strength and biological development has presented lower coeicients when compared to upper limbs explosive strength. Till et al 5 did not verify interaction efect for maturational group x time efect for vertical jump when they compared annually young rugby players performance in respective categories (under 13, under 14 and under 15) according to maturational stage.…”
Section: Discussionmentioning
confidence: 94%
“…De acordo com Cabral et al, (2013), para se desenvolver talentos desportivos, é imprescindível a consideração de diferentes variáveis, tais erros ocorrem principalmente quando se ignora fatores de grande influência como por exemplo, o estágio maturacional dos atletas. Treinadores e professores devem ser cuidadosos com os processos como crescimento e maturação, sendo que estes estão ligados à evolução do desempenho motor na infância e na adolescência.…”
Section: Resultsunclassified
“…Evidências apontam que a maturação se relaciona com a aptidão física de jovens (Cabral, Cabral, Medeiros, Alcatara, & Dantas, 2013a;Cabral et al, 2016;Dantas et al, 2016). De fato, modificações estruturais e metabólicas ocorrem ao longo do processo maturacional e sugerem aumento da produção de força muscular (Lexell et al, 1992;Kaczor et al, 2005;Cole et al, 2015).…”
Section: Tabelaunclassified